Self-Medication and Antimicrobial Resistance: A Survey of Students Studying Healthcare Programmes at a Tertiary Institution in Ghana - Owusu-Ofori, Alex K.; Darko, Eric; Danquah, Cynthia A.; Agyarko-Poku, Thomas; Buabeng, Kwame Ohene (Frontiers in Public Health, 2021)
Objectives: Antimicrobial resistance (AMR) is one of the biggest challenges facing mankind. Inappropriate uses of antibiotics including self-medication promote the increase and spread of AMR. Self-medication has not been well-studied among students. This study was undertaken to determine students of healthcare programmes self-medication practices and attitudes in relation to AMR. Materials and Methods: This was a cross-sectional survey that used a pretested self-administered questionnaire to elicit responses from first-year students of healthcare programmes at the Kwame Nkrumah University of Science and Technology, Ghana from January 2018 to August 2019. Results: Two hundred and eighty students were recruited with 264 of them returning the questionnaire, giving a response rate of 94.3%. Majority were female (68.9%) and participants ages ranged from 16 to 34 years with a mean age (SD) of 19.5 (1.88) years. 136 students (56.2%) had previously purchased antibiotics without a prescription and 78.3% expressed satisfaction with the outcome of self-medication. Amoxicillin (78%) was the most frequent antibiotic bought without a prescription. Majority (76.3%) agreed that self-medication can lead to AMR. Majority (77.0%) believed that antibiotic abuse is a problem in Ghana and 94.8% agreed that the introduction of a course in the University on the rational use of antibiotic will help improve student's knowledge and practices. Conclusion: Self-medication is common among participants despite their knowledge that inappropriate use of antibiotic may lead to resistance. Innovative ways including the introduction of new curricula may help to improve knowledge and to curb wrong attitudes and practices related to antibiotic misuse and ultimately to overcome the problem of AMR.